PREDIKSI KEBANGKRUTAN MODEL SPRINGATE PADA INDUSTRI TELEKOMUNIKASI - Riani Fifrianti; Perdana Wahyu Santosa (Universitas YARSI, 2019)
This study purposes to analyze of corporate bankruptcy prediction of telecommunication industry in Indonesia with Springate model. The data used in the form of financial statements published by the telecommunications industry at Indonesia Stock Exchange for 2009-2013period. The sampling technique of this study was determined by purposive sampling method for six samples from Indonesia Stock Exchange (IDX). The results using Springate model shows that two companies, PT Bakrie Telecom, Tbk and PT Smartfren, Tbk could potentiallybankrupt in the future and three companies For PT Indosat, Tbk, PT XL Axiata, Tbk and PT Inovisi Infracom, Tbk are classified have financial distress problem. The company that very good results is PT Telekom Indonesia, Tbk and categorized has no bankruptcy problem. Ingeneral analysis telecommunication caompany have no good financial condition because business risk and financial risk are higher relatively than other industry.